Kinderstube des Kapitalismus? Monetäre Erziehung im 18. und 19. Jahrhundert - Maß, Sandra (Veröffentlichungen des Deutschen Historischen Instituts London/ Publications of the German Historical Institute London, 2018)
Nursery of Capitalism examines the relationship between children and money in the 18th and 19th centuries. In the modern era, money came to symbolize both a resource for rationalization and a morally dangerous object. The author reveals that this ambivalence surfaced particularly in educating children to become economic citizens, and thus extends the history of economic subjectivity to include the perspective of children.